2014
DOI: 10.1590/s1809-98232014000200009
|View full text |Cite
|
Sign up to set email alerts
|

Perfil socioepidemiológico e autonomia de longevos em Recife-PE, Nordeste do Brasil

Abstract: Dos processos articulados de transição demográfica e epidemiológica em curso nas últimas décadas no país, decorre o crescimento da população idosa, particularmente do número de idosos longevos, com idade acima de 80 anos. Este processo de envelhecimento da população impõe uma reorganização do Estado e da sociedade, principalmente em relação aos sistemas de saúde e previdenciário. OBJETIVO: Analisar o perfil socioepidemiológico e o grau de autonomia e independência de idosos longevos na cidade de Recife-PE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
37

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 12 publications
1
16
0
37
Order By: Relevance
“…An overall mean of 43.68% was obtained, which corroborated with findings in literature 1,7,8,15 . However, research on the older elderly population remains scarce, and further investment in this area is required, as the aging process has been occurring in an accelerated form.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…An overall mean of 43.68% was obtained, which corroborated with findings in literature 1,7,8,15 . However, research on the older elderly population remains scarce, and further investment in this area is required, as the aging process has been occurring in an accelerated form.…”
Section: Discussionsupporting
confidence: 91%
“…As found in literature 1,2,10 , the older elderly persons included in the survey had several chronic diseases. Literature also describes a high frequency of auditory and visual deficit among the elderly 11,12 , a fact that while not quantified in the present study, was observed, though not described.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This transition has consequences for the health systems and society, for one of the characteristics that makes the epidemiological profile of the elderly particular is the predominance of chronic diseases, of gradual progression and high capacity to affect and reduce the autonomy, and independence of the individual. At some point in the illness, the elderly will seek for the health service and in general, the use is more prolonged than in other stages of life 1,2 .…”
Section: Introductionmentioning
confidence: 99%